Morphology, ecology and management of monochoria vaginalis (Burm.f.) Kunth - Athira G.R (Department of Agronomy , College of Horticulture, 2019)
Knowledge on biology and ecology of weeds and its interaction with rice plays a key role in weed management. In the research programme entitled ‘Morphology, ecology and management of Monochoria vaginalis (Burm. f.) Kunth’, Monochoria vaginalis, a broad-leaved monocot weed of wet land paddy was seen to occur in all the major rice ecosystems of Kerala viz., Kole, Palakkad, Pokkali, and Kuttanad, but was not seen in drier parts. It is an emergent annual hydrophyte herb, and has the potential to grow perennially through rhizomes. The plant showed great morphological variation with location, due to the prevailing ecological situation including soil factors. Monochoria grew vigorously with increased soil fertility and favoured slightly acidic condition, but could not tolerate high salinity.